(untitled) (Bangladesh Journal of Agricultural Research, 2010)
Five species of marine a1gae were collected from Saint Martin’s island, identified and biochemical analyses were carried out in BCSIR Laboratories, Chittagong. Biochemical composition were analysed to evaluate its food value and also to find out variation in composition during the period of investigation. The protein content of Sargassum coriifolium was 16.07%, whereas in Padina ltenuis that was estimated at 8.32%. The percentage of fat in Sargassuni coriitolium along with the other sea weeds was 0.5%. It was found that major of the biochemical parameters of these sea weeds were higher except the protein contents than that of Spirulina. The carbohydrate content in Dictyota dichotoma (38.94%) was lower among these sea weeds, but more than that of Spirulina. Carbohydrate contents were higher (56.29%) in Hypnea musciformis. Mineral contents as well as other parameters, especially carbohydrate contents were higher in these algae than that of Spirulina. Key Words: Collection; identification; biochemical analyses; sea weeds. DOI: 10.3329/bjar.v34i1.5754 Bangladesh J. Agril. Res. 34(1) : 59-65, March 2009